The response of TNF-α, IL-6 serum levels and lipid profiles to two aerobic training frequencies with the same volume in obese middle-aged women with type 2 diabetic - ali rajabi; ali akbarnejad; Marefat siahkohian; morteza yari (Shahid Beheshti University, 2021)
Purpose: The aim of this study was to comparison of the effect of two different frequencies of aerobic exercise with the same volume and detraining period on the levels of IL-6, TNF-α and lipid profiles in obese middle-aged women with type 2 diabetes.Methods: Thirty-six obese women age?? with type 2 diabetes were randomly divided into three groups of 12 equal members (Group I = three sessions and group two = six sessions per week, with the same volume). Subjects in Groups I and II performed aerobic training for eight weeks with an intensity of 60 to 75% of the maximum heart rate and the same volume. Samples were taken Pre-test, 48 hours and two weeks after the last training session. Biochemical variables were measured by ELISA method. The repeated measure of Analysis of Variance (ANOVA) with Bonferroni's post hoc test was used to evaluate intra-group changes and One-way ANOVA with post-test Tukey test were used to evaluate the inter-group outcomes at each stage.Results: After eight weeks of interventions, the intergroup results showed that TNF-α, IL-6, TG and total cholesterol were only significantly reduced in Group I (P <0.05). Also, the between-group results showed a significant difference between groups one with control, and I with two in the above variables (P < 0.05). However, there was no significant difference between the group two with control in the post-test and detraining stages (P <0.05). And there was no significant difference between group two and control in post-test and detraining stages (P <0.05). Moreover, results in weight, body fat and BMI variables were only significantly reduced in Group I (P <0.05).Conclusion: The effect of exercise training with a longer duration than the frequency in short-term training sessions was better in controlling the IL-6, TNF-α and lipid profiles in obese women with type 2 diabetes.